ASEAN Mechanism in Disaster Management: A Case Study of Disaster Management in Indonesia 2010-2020 - Suwarti Sari (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2022)
The geographical location of the Southeast Asia region, which is between an intercontinental fault, two oceans, and the Pacifc Ring of Fire, has implications for the probability of the region’s vulnerability to natural disasters. Therefore, how Southeast Asian countries deal with this problem becomes an interesting subject of study. The awareness among Southeast Asian countries of the necessity for collective eﬀorts in disaster mitigation and disaster management is closely related to the ASEAN Way mechanism. This paper discusses environmental security by looking at the ASEAN mechanism in disaster management and the case studies of disasters that occurred in Indonesia. Employing the concept of cohesion, the signing of the AADMER and the establishment of the AHA Centre became a positive signal of group cohesion. This study fnds that there is a contradiction between the ASEAN Way and the disaster management mechanism among ASEAN member states in their application. Still, on the one hand, it strengthens the cohesion of ASEAN member states. The ASEAN Way prohibits any intervention from member states against aﬀected states except at the states’ request with the urgency of collective disaster management. However, cohesion among member states is determined by the behavior of each state, considering the complexity of the inﬂuencing factors. Letak geografs kawasan Asia Tenggara yang berada di antara patahan-antarbenua, dua samudera serta bentangan Cincin Api Pasifk memiliki implikasi terhadap probabilitas kerentanan kawasan tersebut dalam menghadapi bencana alam. Kesadaran negara-negara Asia Tenggara tentang perlunya upaya kolektif dalam melakukan mitigasi bencana dan manajemen bencana berkaitan erat dengan mekanisme ASEAN Way. Tulisan ini membahas mengenai keamanan lingkungan yang dikaji dengan melihat mekanisme ASEAN dalam penanggulangan bencana dengan studi kasus bencana yang terjadi di Indonesia. Menggunakan konsep kohesi, penandatanganan AADMER dan pembentukan AHA Centre menjadi sinyal positif pembentukan kohesi kelompok. Hasil penelitian menemukan bahwa antara ASEAN Way dengan mekanisme penanganan bencana antar negara anggota ASEAN terlihat bertolak belakang dengan aplikasinya, namun di satu sisi semakin memperkuat kohesi anggota ASEAN. ASEAN Way melarang adanya campur tangan negara anggota terhadap negara terdampak kecuali atas permintaan negara tersebut dengan urgensi penanganan bencana secara kolektif. Meskipun demikian, kohesi di antara para negara anggota ditentukan pula oleh perilaku masing-masing negara, mengingat faktor-faktor yang mempengaruhinya pun cukup kompleks